The Principle Of Politeness In Sinking Of The Van Der Wijck Ship - Salma Rosyana; Eka Fadilah; Yohanes Kurniawan Winardi (Seminar Nasional Ilmu Terapan, 2022)
In Sinking of the Van Der Wijck Ship. This study aimed to explain the compliance and violation of Principle of politeness in Sinking of the Van Der Wijck Ship. This author used a qualitative method. The data source of the researcher came from the film “Sinking of the Van Der Wijck Ship”. To collect the data, researcher watched, listened the film and read the film script. The data analysis and the results will be presented descriptively. Based on the conversation, the researcher only took the utterance, analyzed the utterance and put it into a table. The aims were to make it easier to classify data. Then the researcher divided the utterance containing compliance and violation of language politeness. The researcher found that total of 31 maxims of compliances and violations. The compliances are 2 tact maxims, 6 generosity maxims, 4 approbation maxims, 5 modesty maxims, 3 agreement maxims, and 4 sympathy maxims. While the violations are 2 tact maxims, 2 modesty maxims, 3 agreement maxims and no generosity maxim, approbation maxim, and sympathy maxim.